An Analysis of Leadership with Changes in the 4ir Organizational Environment in the World of Education - Medya Apriliansyah (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The development of the world of education in the Era of the Industrial Revolution 4.0 requires the integration of technology used in the world of learning. This of course needs to be followed up with the adjustment of the new curriculum in accordance with current developments. To be able to follow this development, higher education as a place to gain knowledge has an important role in producing superior human resources in this 4.0 era, so a curriculum is needed that is designed to keep up with the changing times that are constantly developing. This is where the role of the Leadership of a Higher Education is in carrying out their duties as a leader to bring this Higher Education to produce human resources who can adapt quickly to all the developments of the times.